GLOBALIZAÇÃO: um modelo de desenvolvimento a serviço da emancipação e da soberania? - Cãndida Costa (Universidade Federal do Maranhão, 2006)
The main characteristics of the process of globalization of the economy and its repercussions in the cultural plan and politician are analyzed, with emphasis in the sovereignty of the State and the citizens. The subordinated insertion of Brazil in the globalization and the necessity of construction of alternatives are distinguished. One concludes that the globalization is a choice process, that if delineates and defines in the plan of the politics.